Dual immunological and proliferative regulation of immune checkpoint FGL1 in lung adenocarcinoma: The pivotal role of the YY1–FGL1–MYH9 axis - Tang, Xi-Yang; Xiong, Yan-Lu; Zhao, Ya-Bo; Yang, Jie; Shi, An-Ping; Zheng, Kai-Fu; Liu, Yu-Jian; Shu, Chen; Jiang, Tao; Ma, Nan; Zhao, Jin-Bo (Frontiers in Immunology, 2022)
Rational: Lung cancer is the most common tumor worldwide, with the highest mortality rate and second highest incidence. Immunotherapy is the major treatment for lung adenocarcinoma (LUAD); however, it has relatively low response rate and high incidence of adverse events. Herein, we explored the therapeutic potential of fibrinogen-like protein 1 (FGL1) for LUAD. Methods: Data from GEPIA and ACLBI databases were assessed to explore gene–gene correlations and tumor immune infiltration patterns. A total of 140 patients with LUAD were recruited; intratumoral and paired peritumoral samples, as well as serum samples were collected. FGL1 levels in the serum and cellular supernatant were determined by enzyme-linked immunosorbent assay. In vitro and in vivo experiments were performed to assess the effect FGL1 on the proliferation of LUAD cells. Cocultures were performed to explore the effect of FGL1 knockdown in lung cancer cells on T cells, concerning cytokine secretion and viability. PROMO and hTFtarget databases were used for transcription factor prediction. Quantitative polymerase chain reaction (qPCR), chromatin immunoprecipitation, and dual luciferase reporter assays were performed to validate the identified transcription factor of FGL1. Immunoprecipitation, mass spectrometry and gene ontology analysis were performed to explore the downstream partners of FGL1. Results: FGL1 expression in LUAD was positively associated with PDL1, but not for PD1 expression. Moreover, FGL1 was positively associated with the CD3D expression and negatively associated with FOXP3, S100A9, and TPSB2 within the tumor site. FGL1 promotes the secretion of interleukin-2 and tumor necrosis factor-α by T cells in vitro, simultaneously inducing their apoptosis. Indeed, YY1 is the upstream molecule of FGL1 was found to be transcriptionally regulated by YY1 and to directly by to MYH9 to promote the proliferation of LUAD cells in vitro and in vivo. Conclusions: FGL1 is involved in the immunological and proliferative regulation of LUAD cells by controlling the secretion of important immune-related cytokines via the YY1–FGL1–MYH9 axis. Hence, targeting FGL1 in LUAD may pave the way for the development of new immunotherapies for tackling this malignancy.